2013
DOI: 10.1364/oe.21.000190
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniformly correlated partially coherent pulses

Abstract: We consider partially coherent plane-wave pulses with non-uniform correlation distributions and study their propagation in linear second-order dispersive media. Particular models for coherence functions are introduced both in time and frequency domains. It is shown that the maximum peak of the pulse energy can be accelerating or decelerating and also self-focusing effects are possible due to coherence-induced propagation effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…That is, the mean temporal intensity and the spectral density of the pulse train are both Gaussian functions, as are the two-time degree of * matias.koivurova@uef.fi temporal coherence and the two-frequency degree of spectral coherence, which both depend on the appropriate coordinate difference only. Considering some of the more exotic correlation functions, one can readily produce similar effects in time domain as one has in the spatial domain, including acceleration of the intensity peak, pulse self-splitting, and pulse flat topping [44][45][46][47]. Out of these, temporal self-splitting is of potential interest in optical data transmission, since it may open up the possibility to encrypt data in a way that unravels itself upon propagation.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the mean temporal intensity and the spectral density of the pulse train are both Gaussian functions, as are the two-time degree of * matias.koivurova@uef.fi temporal coherence and the two-frequency degree of spectral coherence, which both depend on the appropriate coordinate difference only. Considering some of the more exotic correlation functions, one can readily produce similar effects in time domain as one has in the spatial domain, including acceleration of the intensity peak, pulse self-splitting, and pulse flat topping [44][45][46][47]. Out of these, temporal self-splitting is of potential interest in optical data transmission, since it may open up the possibility to encrypt data in a way that unravels itself upon propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Gori et al discussed the sufficient condition for devising a genuine cross-spectral density matrix of an electromagnetic stochastic beam [3]. Based on their pioneer work, a variety of partially coherent beams with different CDOCs (or SDOCs) were recently introduced [4][5][6][7][8]. Lajunen and Saastamoinen introduced a partially coherent beam or a partially coherent pulse with nonuniform correlation distribution [4,5], and it has been demonstrated that such beams display some extraordinary propagation characteristics such as self-focusing and a lateral shift of the intensity maximum [4][5][6][7][8].…”
mentioning
confidence: 99%
“…Based on their pioneer work, a variety of partially coherent beams with different CDOCs (or SDOCs) were recently introduced [4][5][6][7][8]. Lajunen and Saastamoinen introduced a partially coherent beam or a partially coherent pulse with nonuniform correlation distribution [4,5], and it has been demonstrated that such beams display some extraordinary propagation characteristics such as self-focusing and a lateral shift of the intensity maximum [4][5][6][7][8]. Sahin et al introduced a partially coherent beam whose SDOC is modeled by a multi-Gaussian distribution, and found that it produces a flat-topped beam spot in the far field, although its source intensity has a Gaussian beam profile [9,10].…”
mentioning
confidence: 99%
“…However, the only model beam that not being of uniform correlation (e.g., Schell-model correlation) is the spatially varying correlated sources, proposed in [10,11]. In recent years, more and more attention has been paid to these beams with special correlation distribution [12][13][14][15][16][17], due to their interesting features, such as locally sharpened and laterally shifted intensity maxima [4]. The behavior of scalar beams of nonuniform correlation, in isotropic random media, was explored in [12], which introduced a class of electromagnetic beams with nonuniform correlation distribution [5].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental realization of a NUC partially coherent beam was reported in [15]. In addition, plane-wave pulses with nonuniform correlation distributions, and their propagation in dispersive media, have also been investigated [16,17].…”
Section: Introductionmentioning
confidence: 99%